THE ROLE OF BHABINKAMTIBMAS TO PREVENT THE DISSEMINATION OF RADICAL TERRORISM IN THE JURISDICTION OF POLRES KUDUS - Bagas Satya Haprabu (Advances in Police Science Research Journal, 2019)
This research was motivated by the dissemination of radical terrorism in the jurisdiction of the Polres Kudus which was related to the case series of terrorism that have occurred in Indonesia. Even to the point of generated hatred both through social media and radical mass organizations in society. This was the task of the Satbinmas Polres Kudus through Bhabinkamtibmas as the frontliners. However, the legal basis and guidelines for the implementation of counter-radicalization tasks that have not been explained in detail and the material used were still conceptual as obstacles and obstacles for Bhabinkamtibmas in carried out its duties. This research aimed to describe the dissemination of radical terrorism, the role of Bhabinkamtibmas to prevent the dissemination of radical terrorism, and what factors influenced the role of Bhabinkamtibmas. The research used role theory, pro-active police iceberg theory, and crime prevention theory. The concepts used in this research were Bhabinkamtibmas, the concept of radicalism, counter-radicalization, and the factors that affected the prevention of radical terrorism. This research used a qualitative approach with case studies. The methods of data collection used in this research were interviews, observation, and document study. This research found the dissemination of radical terrorism in the jurisdiction of the Polres Kudus caused by the existence of former terrorist convicts. In addition, there were mosques, Islamic boarding schools, mass organizations, and radical books that became the media for radical terrorism. The role of Bhabinkamtibmas to prevent the spread of radical terrorism used a counter-radicalization. They were promotive dan preventive strategies. The main role of Bhabinkamtibmas to prevent the dissemination was affected by factors consisting of six elements. There were man, money, methods, material, machine, and markets. Based on the results in this research, the authors suggest the judicial review of the legal basis and guidelines for the implementation of Bhabinkamtibmas duties, the utilization of the routine activities of the Polres Kudus, the fulfillment of facilities and infrastructure with the Bhabinkamtibmas budget, improving the quality of Bhabinkamtibmas personnel, as well as the need for coordination and cooperation between the Police and Forkopimda ranks and other agencies related in Kudus Regency in limiting the space for the spread of radical terrorism.